Prevalence and Associated Risk Factors of Visual Impairment among Children at Ibn Al-Haitham Eye Hospital in Baghdad,Iraq: A Cross-sectional Study - Baydaa Jaber Shamran; Zainora Mohammed; Hassenien Shuber; Mohd Harimi Abd Rahman; Norliza Mohamad Fadzil (Journal of Clinical and Diagnostic Research)
Introduction: Childhood Visual Impairment (VI) extends beyond poor vision, affecting psychological wellbeing, educational progress and social development. These challenges can persist into adulthood, significantly influencing overall quality of life. However, data on childhood VI in Iraq remain limited. Filling this gap is essential for developing effective health interventions that can enhance outcomes for affected children. Aim: To determine the prevalence, causes and associated risk factors of VI among children aged 6 to 15 years. Materials and Methods: A cross-sectional study was conducted at the Ibn Al-Haitham Teaching Eye Hospital in Baghdad, Iraq from October 2023 to May 2024, which included children aged 6 to 15 years. The participants underwent a comprehensive vision assessment to determine visual status and refractive error. Those who had Best-Corrected Visual Acuity (BCVA) worse than 6/12 were referred to an ophthalmologist to determine the cause of reduced vision. Data on socio-demographic factors and risk factors for VI were collected using a structured questionnaire. These include age, gender, residential area, family income and family history (parents’ age, educational backgrounds and history of refractive error). Results: A total of 508 children, with a mean age of 9.31±2.69 years, were included in the analysis. VI was determined based on presenting visual acuity, with a prevalence of 95 (18.7%). The main causes of vision impairment were uncorrected refractive errors, cataracts and amblyopia. Multivariate analysis showed a high risk of VI among children living in urban areas (adj. OR: 2.50; 95% CI: 1.43-4.40; p-value=0.001). Meanwhile, lesser odds of VI were found among those whose fathers had a secondary education (adj. OR: 0.27; 95% CI: 0.14-0.53; p-value <0.001), tertiary education (adj. OR: 0.10; 95% CI: 0.04-0.21; p-value <0.001), or were myopic (adj. OR: 0.30; 95% CI: 0.17-0.52; p-value <0.001). Conclusion: This study revealed that uncorrected refractive error was the leading cause of VI among children in Iraq. The analysis of risk factors associated with VI underscores the significant impact of socio-demographic characteristics, particularly area of residence and parental education. Therefore, enhancing access to eye care services and implementing awareness programmes to encourage health-seeking behaviours are essential for improving visual health outcomes among children in Baghdad, Iraq.